Inclusion of hypocretin-1 improved performance of poor sleep quality prediction for elderly patients with acute ischemic stroke: a prospective cohort study - Fu, Ting; Zhang, Weiwei; Guo, Rongrong; He, Shuang; Yu, Saiying; Wang, Huiying; Zhang, Yunfeng; Wu, Ying (Frontiers in Aging Neuroscience, 2025)
BackgroundHypocretin-1 is a vital neurotransmitter in regulating the sleep–wake cycle and provides neuroprotection against cerebral ischemia. We aims to develop a poor sleep quality predictive model for elderly population with acute ischemic stroke.MethodsA total of 183 consecutively elderly patients were included in the prospective cohort study. Sleep quality was assessed by the Pittsburgh Sleep Quality Index (PSQI). Cerebrospinal fluid samples were taken within 24 h of acute ischemic stroke onset. After selecting optimal predictors via univariate analysis and bootstrapped stepwise logistic regression, the predictive model was developed. The models were internally validated and evaluated comprehensively via discrimination, calibration, and clinical utility.ResultsThe prevalence of poor sleep (PSQI >7) was 64.5% among elderly individuals experiencing acute ischemic stroke. The study developed a predictive model using hypocretin-1, hypertension, stroke history, the National Institutes of Health Stroke score, and depression. Adding hypocretin-1 (as continuous variable) significantly improved the model performance greatly, as the area under the receiver operating characteristic curve increased from 0.799 to 0.845 (p < 0.001). The optimal cutoff value for hypocretin-1 was 74.94 pg/mL. Adding hypocretin-1 (as binary variable) significantly improved the model performance greatly, as the AUC increased from 0.799 to 0.857 (p < 0.001).ConclusionReduced cerebrospinal fluid levels of hypocretin-1 at admission were an independent poor sleep quality predictor and the model demonstrated superior performance. The combination of hypocretin-1 could offer valuable prognostic information for post-stroke sleep quality in elderly patients with acute ischemic stroke.